Leadership in Change Management from an Islamic Perspective - Habib, Muhammad Fahmi (Universitas Dehasen Bengkulu, 2024)
All types of companies require leadership, which is an essential component of the management process. By influencing and directing others, leaders organize and utilize available resources to maximize employee performance. Any attempt made by a person to influence the behavior of a person or group is referred to as leadership. trying to influence this behavior to meet personal or organizational goals. Since leadership is a key activity in achieving organizational goals, leadership has a significant impact on how well an organization performs. As Allah states in Surah Al-A'raf verse 129, leadership should be positioned in every mission (task) of life and devotion (worship) of every person as a successor in his country. Changes are happening rapidly nowadays, and every company